(untitled) (CIPEEX, 2026)
Introduction: Breast cancer is one of the most incident malignant neoplasms in Brazil. About 10% of the cases have a hereditary origin, mainly associated with mutations in the BRCA1 and BRCA2 genes. Genetic mapping enables early diagnosis, personalized therapeutic approaches, and preventive measures. However, gaps in medical knowledge regarding the applicability of this tool may compromise access for eligible patients and delay diagnoses. Objective: To investigate the rate of oncologists, mastologists, and geneticists who know about genetic mapping in the therapeutic strategy of patients with breast cancer in Goiás. Method: This is an observational, cross-sectional, exploratory, quantitative, descriptive, population-based study conducted with 16 physicians working in Goiás, through an electronic questionnaire. Statistical analysis was performed in SPSS using descriptive statistics and the Chi-square test. Results: The sample was mostly composed of mastologists and oncologists, predominantly male, with a mean age of 40 years, working mainly in Goiânia. Among the participants, 93.75% reported being aware of genetic mapping applied to breast cancer therapy. The findings indicate that the high prevalence of knowledge may be related to the specialized profile of the sample and to Goiás’ pioneering role in implementing free genetic testing, although an informational gap regarding the free-of-charge aspect was identified. Conclusions: The level of knowledge is high and represents a promising advance. Nevertheless, training is necessary to ensure full practical application, expanding equitable access and reducing breast cancer morbidity and mortality.